(untitled) (MMIT Proceedings, 2025)
Modern information and communication technologies (ICT) play a key role in the transformation of the education system. The article discusses the directions of introducing ICT into the educational process of Uzbekistan, provides specific examples of ongoing projects, and assesses their impact on accessibility and quality of education.